2011
DOI: 10.2298/bah1103345k
|View full text |Cite
|
Sign up to set email alerts
|

Effect of two natural antioxidants in combination with edible packaging on stability of low fat beef product stored under frozen condition

Abstract: The chemical composition, expressible water (EW), water holding capacity (WHC), pH value, total acidity (as lactic acid), thiobarbituric acid (TBA), aerobic plate count, and sensory evaluation were determined in order to evaluate the effect of two different natural antioxidants combined with edible packaging on the stability of low fat beef product stored frozen for six months. The data showed that there were no changes in the chemical composition as a result of the addition of antioxidants. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 18 publications
4
17
0
2
Order By: Relevance
“…Juiciness scores showed a decreasing trend with increasing storage period, which might be due to loss of moisture from the products during aerobic storage. The present results corroborated with the finding of Kenawi et al (2011) that juiciness score decreased in Rosemary and Green tea treated beef products under frozen condition. Juiciness scores were comparable in control, T 2 and T 3 samples than T 1 , because T 1 sample was kept in refrigeration with edible film without any secondary packaging.…”
Section: Sensory Characteristicssupporting
confidence: 92%
See 1 more Smart Citation
“…Juiciness scores showed a decreasing trend with increasing storage period, which might be due to loss of moisture from the products during aerobic storage. The present results corroborated with the finding of Kenawi et al (2011) that juiciness score decreased in Rosemary and Green tea treated beef products under frozen condition. Juiciness scores were comparable in control, T 2 and T 3 samples than T 1 , because T 1 sample was kept in refrigeration with edible film without any secondary packaging.…”
Section: Sensory Characteristicssupporting
confidence: 92%
“…There was significant (P \ 0.05) decrease in TBARS values in T 2 after 10th day of storage on compared to other treatments, which might be due to antioxidant effects of essential oil on lipid oxidation. The similar results were found in beef muscle slices wrapped with milk protein based edible films containing 1.0% (w/v) oregano (Oussalah et al 2004), in fresh chicken sausages treated with essential oils (Sharma et al 2017), and in Rosemary and Green tea treated beef products (Kenawi et al 2011). Park et al (2012) also reported lower TBARS values of raw beef patties containing 3.0% eugenol, packaged in LLDPE/Corn zein laminates.…”
Section: Tbarssupporting
confidence: 76%
“…Changes in such parameter reflect the extent of water holding capacity (WHC) of meat and directly affect yield of meat during cooking. These results agreed with Kenawi et al (2011) and Kamel (2015). They recorded loss of moisture combined with increasing of water holding capacity of meat upon longer storage due to the activity of protolytic enzymes.…”
Section: Effect Of Freezing Storage At -18p O P C On Some Physicochemsupporting
confidence: 92%
“…Natural antioxidant containing enrobed chevon balls gained highest score of overall palatability during the refrigeration storage period. These findings were in corroboration with the results reported by Biswas et al, (2003) in enrobed pork patty, Bhat et al, (2011) in chicken meat balls, Kenawi et al, (2011) in low fat beef product and Karim et al, (2012) in chicken patties.…”
Section: Sensory Attributessupporting
confidence: 90%